Decomposition of the budget process of the territorially largest G20 countries - S.V.; V.V.; T.M. (Економіка, управління та адміністрування)
The success of reforming the budget sphere of Ukraine directly depends on taking into account the budgetary experience of the most developed countries in the world, which are represented by the so-called group of 20. In continuation of previous studies that covered the experience of the most powerful G20 countries - the USA, the People's Republic of China and Japan - the article presents a decomposition of the budget process of Brazil, Canada, Australia, Mexico, India, Turkey by studying the elements of budget systems and budget processes of the above countries. The authors identified and analyzed the budget legislation of the above-mentioned countries, determined the components of the budget systems of the latter, identified the powers of all branches of government regarding the budget process in Brazil, Canada, Australia, Mexico, India, Turkey, described the step-by-step components of the budget process in these countries, worked out budget principles in principles of budgeting and principles of the budget process in Brazil, Canada, Australia, Mexico, India, Turkey. The decomposition of the budget process of Brazil, Canada, Australia, Mexico, India, Turkey, as well as the following comparative analysis, allowed us to draw a conclusion about the strengths of the budget process of these countries (which is manifested in its clear regulation, systematization, accountability, openness, coordination and discussion , controllability, etc.), and weak (which is manifested in the absence of instructions regarding budget surplus, as well as the absence of the concept of budget security). On the basis of the obtained results and realities in the field of public finances of Ukraine, a proposal was put forward to strengthen control, agree and discuss the boundaries of the domestic budget process, as well as further development of budget security, as an important element of managing the budget process.